STRATEGI PEMBANGUNAN EKONOMI DESA LARANGAN DALAM RANGKA PENCAPAIAN TUJUAN SDGs - Novalia Eka Pravitasari; Isna Fitria Agustina (Journal Publicuho, 2025)
This study aims to analyse the economic development strategy implemented by Larangan Village in achieving the Sustainable Development Goals (SDGs). A qualitative approach was employed, utilising interviews, observations, documentation, and literature review. The analysis is based on Kotten's strategy theory in Salusu (2008), which includes three key indicators: organisational strategy, resource support strategy, and program strategy. The findings reveal discrepancies in data between the village and central government, limited human resources for SDGs data entry, and the need for more locally-adapted technology. The study concludes that achieving SDGs effectively requires strengthening organisational coordination, providing technical training, and applying simplified digital systems. With integrated and data-driven strategies, Larangan Village’s economic development can become more inclusive and sustainable.